2002
DOI: 10.1006/adnd.2002.0879
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure Radiative Transitions in C Ii and C Iii Using the Breit–pauli R-Matrix Method

Abstract: Extensive sets of radiative transitions in C II and in C III are obtained using the relativistic Breit-Pauli R-matrix (BPRM) method. In comparison with other accurate methods that can be applied to relatively few transitions, the BPRM method enables calculations of a large number of transitions with comparable accuracy for most of them. The present work reports large-scale calculations for two important ions obtaining 127 and 206 bound fine structure energy levels, resulting in 1681 and 4202 dipole allowed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…As a result, they observed only three weak peaks corresponding to excitation from the 2s2p 2 4 P term, while the remaining 35 measured peaks were associated with absorption from the ground 2s 2 2p 2 P term. The identifications were assisted by their own extensive Cowan code calculations and by comparisons with the R-matrix calculations of Nahar (1995). Kjeldsen et al (1999Kjeldsen et al ( , 2001 reported observed spectral lines in the range between 25 and 51 nm and stated that the absolute uncertainty of the measured peak energies is 0.015 eV, which corresponds to an uncertainty of 0.008-0.31 nm in wavelength.…”
Section: The Spectrum Of the Ic 418 Nebula Spectramentioning
confidence: 99%
“…As a result, they observed only three weak peaks corresponding to excitation from the 2s2p 2 4 P term, while the remaining 35 measured peaks were associated with absorption from the ground 2s 2 2p 2 P term. The identifications were assisted by their own extensive Cowan code calculations and by comparisons with the R-matrix calculations of Nahar (1995). Kjeldsen et al (1999Kjeldsen et al ( , 2001 reported observed spectral lines in the range between 25 and 51 nm and stated that the absolute uncertainty of the measured peak energies is 0.015 eV, which corresponds to an uncertainty of 0.008-0.31 nm in wavelength.…”
Section: The Spectrum Of the Ic 418 Nebula Spectramentioning
confidence: 99%